Cardiac Fibrotic Remodeling on a Chip with Dynamic Mechanical Stimulation - Kong, Ming; Lee, Junmin; Yazdi, Iman K.; Miri, Amir K.; Lin, Yi-Dong; Seo, Jungmok; Zhang, Yu Shrike; Khademhosseini, Ali; Shin, Su Ryon (WILEY, 2019)
Cardiac tissue is characterized by being dynamic and contractile, imparting the important role of biomechanical cues in the regulation of normal physiological activity or pathological remodeling. However, the dynamic mechanical tension ability also varies due to extracellular matrix remodeling in fibrosis, accompanied with the phenotypic transition from cardiac fibroblasts (CFs) to myofibroblasts. It is hypothesized that the dynamic mechanical tension ability regulates cardiac phenotypic transition within fibrosis in a strain-mediated manner. In this study, a microdevice that is able to simultaneously and accurately mimic the biomechanical properties of the cardiac physiological and pathological microenvironment is developed. The microdevice can apply cyclic compressions with gradient magnitudes (5-20%) and tunable frequency onto gelatin methacryloyl (GelMA) hydrogels laden with CFs, and also enables the integration of cytokines. The strain-response correlations between mechanical compression and CFs spreading, and proliferation and fibrotic phenotype remolding, are investigated. Results reveal that mechanical compression plays a crucial role in the CFs phenotypic transition, depending on the strain of mechanical load and myofibroblast maturity of CFs encapsulated in GelMA hydrogels. The results provide evidence regarding the strain-response correlation of mechanical stimulation in CFs phenotypic remodeling, which can be used to develop new preventive or therapeutic strategies for cardiac fibrosis.